KONTRIBUSI PAHAM KEAGAMAAN PENGUSAHA TERHADAP TINGKAT PRODUKSI BATU MERAH DI KABUPATEN PINRANG - Wahid, Abdul (Kuriositas: Media Komunikasi Sosial dan Keagamaan, 2016)
This study discusses about how to the notion Religious Enterpreneur Contributions to the brown stone Production Rate Pinrang. In testing associative product moment correlation analysis. The results of the study found; First, the level of religious understanding brown stone entrepreneurs in Pinrang descriptive classified by category quite well. Second, the performance level of industrial entrepreneurs in the brown stone Pinrang classified based on the results of the descriptive analysis of the high category, or both. Third, relationship or employer contributions toward religious understanding of performance levels in the brown stone industry Pinrang based on the results of manual analysis and analysis of SPSS for windows is very significant. The implications of this study are expected to be input to the local government offices Pinrang especially those related to the variable of religious thought and red stone industry, so as to provide motivation, spirit, and capital assistance to entrepreneurs to develop their businesses.